Антология выдающихся достижений в науке и технике. Часть 2: Открытие и изучение радиоактивности химических элементов - Баранов, М.И. (Електротехніка і електромеханіка, 2011)
A brief outline from the global history of discovery and initial study of radioactivity of chemical elements is given, the phenomenon being of fundamental scientific and engineering significance for mankind.